2012
DOI: 10.2478/v10102-012-0002-9
|View full text |Cite
|
Sign up to set email alerts
|

Damage of testicular cell macromolecules and reproductive capacity of male rats following co-administration of ethambutol, rifampicin, isoniazid and pyrazinamide

Abstract: The necessity to minimize adverse effects of tuberculosis chemotherapy requires a comprehensive evaluation of the effects of antituberculosis drugs on the reproductive system and testicular cell macromolecules. The epidemiological situation of tuberculosis in Central and Eastern Europe is getting worse. Data on adverse effects of antituberculosis drugs are scare concerning particularly their effects on the reproductive system. The aim of the present study was to investigate the potential effect of ethambutol, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…We have previously shown the antifertility effect of anti-tuberculosis medicines in male rats (Shayakhmetova et al, 2012a). It has been reported that the coadministration EMB, INH, RMP and PZA (in therapeutic doses) to male rats during the period of spermatogenesis caused an increase in the rate of thiobarbituric acid reactive substances (TBARS) formation in testes and sperm, decrease of testis glutathione and protein SH-group contents, significant changes in DNA fragmentation, fatal decrease of male fertilizing capacity and fertility, and an increase of pre-and post-implantation embryolethality (Shayakhmetova et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown the antifertility effect of anti-tuberculosis medicines in male rats (Shayakhmetova et al, 2012a). It has been reported that the coadministration EMB, INH, RMP and PZA (in therapeutic doses) to male rats during the period of spermatogenesis caused an increase in the rate of thiobarbituric acid reactive substances (TBARS) formation in testes and sperm, decrease of testis glutathione and protein SH-group contents, significant changes in DNA fragmentation, fatal decrease of male fertilizing capacity and fertility, and an increase of pre-and post-implantation embryolethality (Shayakhmetova et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…The delicate equilibrium between ROS production and recycling is crucial for normal spermatogenesis and its excessive generation causes male infertility [2]. Bee pollen has arisen as a promising agent with the recognition of its antioxidant effects.…”
Section: Discussionmentioning
confidence: 99%
“…Even though rifampicin and isoniazid are wonder drugs in effective management of tuberculosis, certain toxic effects have been documented in humans. The coadministration of ethambutol, isoniazid, rifampicin, and pyrazinamide to male rats during the period of spermatogenesis caused an increase in the level of malondialdehyde (MDA), and the rate of glutathione (GSH) and protein SH-group contents was significantly decreased [2]. Fatal decrease of male fertilizing capacity and fertility was also reported by antituberculosis drugs.…”
Section: Introductionmentioning
confidence: 99%
“…In such situation investigation of these compounds adverse effects becomes of vitally importance. We have previously shown the antifertility effects of anti-tuberculosis medicines combination in male rats with simultaneous increase in cytochrome P-450 2E1 (CYP2Е1) mRNA in their testes [3,4]. It is important to note that series of studies clearly demonstrated inducibility of CYP2E1 in testis, suggesting its possible role in chemicals bioactivation to their toxic metabolites directly in male gonads [4,5,6,7].…”
mentioning
confidence: 99%
“…It remains unclear which one of the four coadministered (ATD) plays a crucial role in testicular CYP2Е1 expression modulation and the development of antifertility effects. Thus, in terms of our above mentioned results [3,4] analysis of potential effects on male gonads of each component of the combination are urgently required.…”
mentioning
confidence: 99%